2014
DOI: 10.1039/c4cp01762e
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of dispersion on surface interactions of cobalt(ii) octaethylporphyrin monolayer on Au(111) and HOPG(0001) substrates: a comparative first principles study

Abstract: A density functional theory study of a cobalt(II) octaethylporphyrin (CoOEP) monolayer on Au(111) and HOPG(0001) surfaces was performed under periodic boundary conditions. Calculations with and without dispersion corrections are performed and the effect of van der Waals forces on the interface properties is analyzed. Calculations have determined that the CoOEP molecule tends to bind at the 3-fold and the 6-fold center sites on Au(111) and HOPG(0001), respectively. Geometric optimizations at the center binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 100 publications
(122 reference statements)
2
68
0
Order By: Relevance
“…Confirmation of complex interaction frameworks at SAM interfaces is found in the weakly interacting porphyrinoid layers deposited on conductive substrates, such as Au(111) and graphite, HOPG [2], where dispersion is found to play a critical role in altering the adsorption and charge distribution. The comparative study between the two different substrates demonstrates that CoOEP bind more strongly to gold than to graphite, enlightening the molecule-substrate interactions in weakly bond interfaces and the role of dispersion forces between molecules and conductive substrates.…”
Section: Case Systems and Trendsmentioning
confidence: 87%
See 1 more Smart Citation
“…Confirmation of complex interaction frameworks at SAM interfaces is found in the weakly interacting porphyrinoid layers deposited on conductive substrates, such as Au(111) and graphite, HOPG [2], where dispersion is found to play a critical role in altering the adsorption and charge distribution. The comparative study between the two different substrates demonstrates that CoOEP bind more strongly to gold than to graphite, enlightening the molecule-substrate interactions in weakly bond interfaces and the role of dispersion forces between molecules and conductive substrates.…”
Section: Case Systems and Trendsmentioning
confidence: 87%
“…The experience in these decades has stated that molecule-substrate must be viewed as a whole. Even in weak-bounded molecular layers [2], the simple change of symmetry induced by adsorption and the induced dipoles can lead to modifications of the molecular and metallic states, affecting the electronic structure at the interface [3][4][5][6]. The static and dynamic characterization on different time scales are crucial for the comprehension of such complex systems, as well as the understanding of the mutual correlation among the structural, opto-magnetic, and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…A first comprehensive study of OEP on substrates using PDFT simulations was reported by Chilukuri et al [96]. It was reported that using standard GGA [45] and LDA [97] functionals would significantly underestimate the adsorption energies of porphyrins on substrates compared to calculations using van der Waals corrected DFT methods like vdW-DF [43,48] or DFT-D3 [53,85].…”
Section: Conformational Studies Of Non-meso-substituted Porphyrins Onmentioning
confidence: 99%
“…PDFT calculations of not porphyrins but porphyrin-based molecules are also studied in the literature. For example, Zhang et al studied the adsorption of Ni(Salophen) molecule on Au(111) surface using vdW-DFT functionals and determined the adsorption energy to be 2.74 eV which is about 2/3 of the adsorption energy of similar porphyrin [96,106] molecules on Au(111). Gurdal et al studied the adsorption of pyrphyrin molecules on Au(111) [107] and Ag (111) [108] surfaces using various GGA and vdW-GGA functionals.…”
Section: Conformational Studies Of Non-meso-substituted Porphyrins Onmentioning
confidence: 99%
See 1 more Smart Citation